2019
DOI: 10.1111/his.14015
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of molecular characteristics into endometrial cancer management

Abstract: Histopathological evaluation including subtyping and grading is the current cornerstone for endometrial cancer (EC) classification. This provides clinicians with prognostic information and input for further treatment recommendations. Nonetheless, patients with histologically similar ECs may have very different outcomes, notably in patients with high‐grade endometrial carcinomas. For endometrial cancer, four molecular subgroups have undergone extensive studies in recent years: POLE ultramutated (POLEmut), misma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
148
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(157 citation statements)
references
References 79 publications
4
148
2
3
Order By: Relevance
“…According to recent studies, MSI-H/hypermutated tumors which include Lynch syndrome cancers and are represented by loss of MMR (Mismatch Repair) through hypermethylation of one of MMR proteins, comprise 25-30% of endometrial carcinomas [15]. Our study revealed a significant percentage of MSI-H tumors (68%) diagnosed by evaluating loss of MSH6 and/or PMS2 expression, which contradicts various research performed on much larger cohorts [8,15,16]. Other parameters of our study correlated with this molecular subgroup similarly with other conducted studies: higher-grade ECs, endometrioid-type histology, moderate/marked TILs, substantial LVSI [8].…”
Section: Resultscontrasting
confidence: 88%
See 3 more Smart Citations
“…According to recent studies, MSI-H/hypermutated tumors which include Lynch syndrome cancers and are represented by loss of MMR (Mismatch Repair) through hypermethylation of one of MMR proteins, comprise 25-30% of endometrial carcinomas [15]. Our study revealed a significant percentage of MSI-H tumors (68%) diagnosed by evaluating loss of MSH6 and/or PMS2 expression, which contradicts various research performed on much larger cohorts [8,15,16]. Other parameters of our study correlated with this molecular subgroup similarly with other conducted studies: higher-grade ECs, endometrioid-type histology, moderate/marked TILs, substantial LVSI [8].…”
Section: Resultscontrasting
confidence: 88%
“…Our study revealed a significant percentage of MSI-H tumors (68%) diagnosed by evaluating loss of MSH6 and/or PMS2 expression, which contradicts various research performed on much larger cohorts [8,15,16]. Other parameters of our study correlated with this molecular subgroup similarly with other conducted studies: higher-grade ECs, endometrioid-type histology, moderate/marked TILs, substantial LVSI [8].…”
Section: Resultscontrasting
confidence: 79%
See 2 more Smart Citations
“…Treatment of EC is usually surgical (hysterectomy and bilateral salpingo-oophorectomy), although a significant minority are offered conservative management in the form of hormonal manipulations, especially women of childbearing age who wish to preserve their fertility [9]. Decisions about adjuvant chemotherapy and radiotherapy are currently based on traditional pathological parameters that lack precision and therefore deny some women with biologically aggressive disease the opportunity to receive life-saving treatments whilst exposing others to unnecessary harms [5,22]. There is, at present, limited evidence to support the routine use of imaging or biochemical testing in the follow-up for EC due mainly to the lack of reliable monitoring tools [5].…”
Section: Introductionmentioning
confidence: 99%